ESTRATÉGIAS PRODUTIVAS E DE GERAÇÃO DE RENDA EM SOLOS DE BAIXA FERTILIDADE NATURAL NO POVOADO DE MATO GROSSO, MUNICÍPIO DE MORROS – MA - MARTINS, Raymara Fernanda Dutra (2024)
In tropical areas, intense weathering and source materials correlated to sedimentary formations attribute low natural fertility to soils, which implies a strong influence on their quality and productivity when used for agricultural activities. This research analyzed low fertility soils in regions subject to intense chemical weathering. The methodology included field research with collection of soil samples, description of soil profiles described according to the procedures in the Field Collection and Description Manual, and analyzed according to the criteria established by the Brazilian Soil Classification System, in addition to questionnaires for farmers locations, meetings with residents and photographic records. In the Mato Grosso community, belonging to the municipality of Morros, Maranhão, where the study was focused, the soils are predominantly poor, a result of weathering. The knowledge developed by farmers regarding soil and the management of their land is influenced by both practical and cognitive aspects. Thus, residents adopt adaptive strategies, such as the traditional use of fire, intercropping and crop rotation. The cultivation of species adapted to soil poverty stands out, such as cassava and beans. The results revealed the importance of these practices to address soil limitations. These findings not only guide local farmers, but are also relevant to inform policies and actions aimed at sustainable agricultural development and the preservation of natural resources in areas with challenging soils, offering a guide for future interventions aimed at the resilience of communities dependent on these lands.